The Effect of a Generative AI-Assisted Blended Learning Model on Students' Self-Regulated Learning and Critical Literacy in Indonesian Language Lessons - Isnainiwati Isnainiwati; Teguh Sumarno (Yayasan Azhar Amanaa Yogyakarta, 2026)
The low level of students' independent learning and text analysis skills demands pedagogical innovation in the digital era. This study aims to analyze the effect of implementing a Generative AI-assisted Blended Learning model on improving students' Self-Regulated Learning (SRL) and Critical Literacy in Indonesian language subjects. A quantitative approach with a quasi-experimental method using a One-Group Pretest-Posttest design was employed. The research sample consisted of 25 eighth-grade students at MTsS Puspa Bangsa, selected using a total sampling technique. Data were collected using a Likert-scale questionnaire to measure students' SRL and an essay test to assess their Critical Literacy skills. The results of the Paired Sample t-Test showed a significant difference between the pretest and posttest scores for both variables (p < 0.05). The average SRL score increased from 62.40 to 81.60, with an N-Gain value of 51.06%, categorized as moderately effective. Meanwhile, the average Critical Literacy score increased from 58.20 to 83.40, with an N-Gain value of 60.29%, categorized as moderately effective. These findings indicate that the implementation of Generative AI-assisted Blended Learning significantly improved students' Self-Regulated Learning and Critical Literacy. The findings suggest that integrating Generative AI into Blended Learning can support students' self-regulation while strengthening their ability to critically analyze and evaluate texts.